Exploring Entrepreneurial English in Digital Information: Harmonizing News Headlines with their Introductions in Phoenix - Akinola, Adeyemi Adewale; Anana, Mariam (Access: An International Journal of Nepal Library Association, 2024)
Entrepreneurial English is very necessary in digital information. This study investigates the place of digital copywriting in harmonizing news headlines and introductions of news in Phoenix. Data were randomly selected from recent news headlines and their introductions. Qualitative research design, Harold Hassell (1949)’s Model of communication and Summative Content Analysis were adopted as research design and theoretical frameworks. The result shows that all news headlines and their introductions in Phoenix capture control analysis, content analysis, medial analysis and effect analysis but some lack audience analysis. Results also show that five (5) headlines and five (5) introductions attracted the attention of the readers because of their contents and contexts; eight (8) were not attention-catching, and two (NH7 and I7) defined their attractiveness due to the audience decisions/choices. Only six (6) items were grammatical while (14) were not. However, copywriting is copiously relegated to the background in digital information on Phoenix. Online information should be written by copywriters so as to minimize or eradicate linguistics blunders of all sorts.